Effective coverage for antiretroviral therapy in a Ugandan district with a decentralized model of care - Scheibe, Florian J. B.; Waiswa, Peter; Kadobera, Daniel; Müller, Olaf; Ekström, Anna M.; Sarker, Malabika; Neuhann, H. W. Florian (© 2013 PLoS ONE, 2017)
This article was published in the PLoS ONE [© 2013 PLoS ONE] and The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0069433